ANTIBIOTIC in vitro SUSCEPTIBILITY OF SUBGINGIVAL BACTERIA IN CANINES WITH MODERATE TO SEVERE PERIODONTAL DISEASE - Vega B., Henry (2014)
The aim of this study was to determine the antibiotic susceptibility of subgingivalbacteria in dogs with moderate to severe periodontal disease. Thirty dogs from fourshelters were sampled using sterile paper sheet tips at the bottom of the periodontalpocket in the fourth premolar and canine teeth of the upper right quadrant. The most frequent bacteria isolated were Porphyromonas gingivalis (50%), Bifidobacterium spp(20%), Prevotella intermedia (16.7%), Staphylococcus spp (30%) and enterobacteria(60%). The highest antibiotic susceptibility from isolated bacteria species was againstimipenem. The susceptibility against other antibiotics depended of the bacterial species.